2007
DOI: 10.1111/j.1399-3089.2006.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation outcome and functional characteristics of young and adult pig pancreatic islets for transplantation studies

Abstract: These data support the conclusion that, in view of the large number of islets needed to maintain normoglycemia after xenotransplantation, organ-source pigs need to reach adult age (>2 yr) before being considered optimal islet donors, in spite of the higher costs involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 48 publications
(68 reference statements)
6
88
0
Order By: Relevance
“…Porcine islets were isolated and purified according to a standard procedure that involved low enzyme concentration, low digestion temperature and minimal mechanical digestion [18]. The overall quality of the islet preparations was evaluated as described in [18]: viability was >95%, purity 82.1±4.5% (n=5) islets/whole tissue, and the mean stimulation index was 4.6±1.7 (n=5). A total of 40,000-100,000 islet equivalents (IEq)/kg was infused into the portal vein under direct vision at laparotomy under general anaesthesia.…”
Section: Porcine Islet Isolation and Transplantation Into Monkeysmentioning
confidence: 99%
“…Porcine islets were isolated and purified according to a standard procedure that involved low enzyme concentration, low digestion temperature and minimal mechanical digestion [18]. The overall quality of the islet preparations was evaluated as described in [18]: viability was >95%, purity 82.1±4.5% (n=5) islets/whole tissue, and the mean stimulation index was 4.6±1.7 (n=5). A total of 40,000-100,000 islet equivalents (IEq)/kg was infused into the portal vein under direct vision at laparotomy under general anaesthesia.…”
Section: Porcine Islet Isolation and Transplantation Into Monkeysmentioning
confidence: 99%
“…Pig islets are also considered more elusive on account of striking fragility, irregular shape, and quick dissociation into small aggregates or single cells during the isolation process (Bottino et al, 2007). Further, several studies have demonstrated great variability of islet capsule, size, and yield from various pig donors (Heiser et al, 1994;Kirchhof et al, 1994;Ulrichs et al, 1995;Meyer et al, 1997;Kim et al, 2007;Kinasiewicz et al, 2011).…”
Section: Selection Of Pig Strainmentioning
confidence: 99%
“…Normally, insulin independence in diabetic NHPs can be achieved when a sufficient islet cell mass (25 000-100 000 islet equivalents (IEQ)/kg recipient body weight) is implanted (Hering et al, 2006;Casu et al, 2008;van der Windt et al, 2009;Thompson et al, 2011a;, which requires pooling of islets from 2-4 adult pig donors or 7-10 neonatal pig donors (Korbutt, 2009). Generally, adult pigs aged >2 years (particularly retired breeders) are preferred as suitable donors, providing a greater number of islets with intact morphology, large size (150-200 μm), and good structure (Dufrane et al, 2005a;2005b;Bottino et al, 2007). Conversely, pancreata from neonatal or young pigs (<6 months) are essentially composed of small islets with a diameter of 50-100 μm (Korbutt et al, 1996;Dufrane et al, 2005a).…”
Section: Adult and Young Pig Isletsmentioning
confidence: 99%
“…of the donor pig has been documented by several groups Surgical Model to markedly influence the islet isolation process, with young, so-called market size pigs (<6 months old) provUntil recently, the anatomy of the pig pancreas was not well documented (11,36,39). Physiologically and ing to be particularly difficult as a source of transplantable islets (7,10,50). Islets from adult pigs (>2 years old) topographically the pig and human pancreata are considered similar.…”
Section: Following Intraductal Pancreas Distension All Extraneousmentioning
confidence: 99%
“…The common bile The age of the donor pig has proved to be a significant factor in the islet isolation process with young, soduct and pancreatic duct openings were included as part of the duodenum segment. This considerably facilitated called market size pigs (<6 months old), proving to be particularly difficult as a source of transplantable islets pancreatic duct cannulation, by avoiding the difficulties encountered with retracted duct identification and can- (7,10,50). Nevertheless, despite these challenges young pigs are favored over retired breeders (>2 years old) due nulation, and preserved early duct branches.…”
Section: Introductionmentioning
confidence: 99%